PENGARUH MEDIA MONTESSORI COUNTING BOARD INTERAKTIF TERHADAP KEMAMPUAN BERHITUNG ANAK DI TAMAN KANAK-KANAK SYUKRA CENDEKIA MADANI - Reyza Mutia Adha; Setiyo Utoyo; Indra Yeni; Tisna Syanita (STKIP Subang, 2026)
This research is motivated by the persistent lack of numeracy skills and low interest in numeracy learning among children. The interactive Montessori counting board is an effective and engaging medium for numeracy learning. This study aims to determine the effect of the interactive Montessori counting board on numeracy skills in children at Syukra Cendekia Madani Kindergarten.This research approach uses a quantitative method with a quasi-experimental approach. The study involved children at Syukra Cendekia Madani Kindergarten. Purposive sampling was used. Class B1 served as the experimental class and Class B2 as the control class, with 10 children in each class. Data collection used a nine-item test, and data analysis used to compare the differences between the two mean scores, leading to a T-test. Data processing used SPPS version 31 for Windows. Based on the post-test hypothesis test, the sig value (2-tailed) was 0.001 < 0.05. This means there is a significant difference between the interactive Montessori counting board and the teacher's treatment on children's counting skills. It can be concluded that the interactive Montessori counting board has an effect on children's counting skills.